1998
DOI: 10.1002/(sici)1099-0682(199802)1998:2<163::aid-ejic163>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Behaviour of the New Multidentate Ligand 3,5-Bis(dimethylaminomethyl)pyridine with Palladium(II) and Platinum(II) Metal Centres

Abstract: The synthesis of the new potentially tridentate ligand 3,5‐bis(dimethylaminomethyl)pyridine (3) is described. Coordination chemistry of this ligand has been investigated with PdII and PtII precursor compounds. Both a bidentate bridging bonding motif and a monodentate bonding mode is observed. The latter compounds incorporate 3 by coordination through the pyridinic N atom only. The former complexes contain ligand 3 bonded to 2 metal centres by bridging through coordination of one trialkyl N donor atom and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…These data reflect the dynamic nature of these complexes, involving inversion at the coordinated sulfur atom, a process frequently observed for similar complexes [13]. To further confirm that this structural motif is retained in the solid state, a single crystal X-ray diffraction study of 2 was carried out 3 . This revealed that the general structure suggested in solution is also found in the solid state.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…These data reflect the dynamic nature of these complexes, involving inversion at the coordinated sulfur atom, a process frequently observed for similar complexes [13]. To further confirm that this structural motif is retained in the solid state, a single crystal X-ray diffraction study of 2 was carried out 3 . This revealed that the general structure suggested in solution is also found in the solid state.…”
Section: Resultssupporting
confidence: 70%
“…In a series of publications, we have reported a large number of transition metal (TM) and lanthanide complexes containing multidentate donor fragments that are commonly referred to as 'pincer' ligands [1]. These species include such organic molecules as 2,6-bis-[(dimethylamino)methyl]pyridine (NN%N) [2], 3,5-bis-[(dimethylamino)methyl]pyridine [3] and the aryl carbanions derived from 2,6-bis[(dimethylamino)methyl]benzene (NCN%) [1,4] or its phosphorous analogues (PCP: Fig. 1) [5].…”
Section: Introductionmentioning
confidence: 99%
“…was described in a previous paper. 20 3,5-Bis(chloromethyl)pyridine, 26 3-(1H-imidazol-1-yl)pentane-1,5-diamine, 27 3-(1H-imidazol-1-yl)pentanedioic acid, 28 and mono 29 were synthesized according to the procedures reported in the literature. The synthetic procedures for Py3NHCD, Im3NHCD and Im2CD are shown below.…”
Section: Methodsmentioning
confidence: 99%
“…Another strategy to obtain 'early-late' heterometallic compounds is the reaction of suitable late TM complexes with the N-ligating site of compounds 5 or 6. Therefore, these molecules were reacted with the cationic Pt complexes [ [35] as well as with the neutral dinitrogen bridged Ru complex 14 [36]. Here, the Ti acetylide could act as an h 1 -coordinated ligand after displacement of H 2 O, MeCN or N 2 , respectively (Scheme 1).…”
Section: Reacti6ity Of 5 and 6 Towards Late Transition Metal Complexesmentioning
confidence: 99%
“…The starting materials {Ti}Cl (1) [11,20] (13) [35] and {Ru}N N{Ru} ( 14) [36] were prepared following published procedures. All other chemicals were purchased from commercial sources.…”
Section: General Remarksmentioning
confidence: 99%